English Renaissance drama and the specter of Spain : ethnopoetics and empire - Griffin, Eric J. (UPCC book collections on Project MUSE., 2009)
Eric J. Griffin discovers the rhetorical strategies through which the Hispanophobic perspectives now known as the Black Legend of Spanish Cruelty were written into English cultural memory.